The significant impact of the most recent European regulations and jurisprudence on fundamental workers' rights in Spain - García Salas, Ana Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
When we refer to the impact of European law on our internal system of fundamental rights, even only in an area such as labor, one might think that the proposed topic is of incomprehensible content for a work of such limited extension. However, it will be enough to approach some of the cases and rights that have been most markedly affected in recent times, and that exhibit, beyond the obligatory submission to the Law emanating from the European institutions, a kind of interaction and reciprocity between both systems. It is thus demonstrated that European influence does not have to be an external or foreign element, but rather converges on the same range of values, principles and rules, naturally acceptable to States, such as Spain, whose Europeanness is found in its very essence.
Keywords: Data protection; secrecy of communications; religious freedom; conscientious objection; equality